Factors affecting electric vehicle adoption intention: The impact of objective, perceived, and prospective charger accessibility - Sylvia He; Shuli Luo; Ka Kit Sun (Journal of Transport and Land Use)
In the era of e-mobility, promoting electric vehicle (EV) usage is considered a policy worth incorporating into a government’s agenda. While accessibility has been broadly recognized as important for user intention to adopt EVs, few studies have considered how accessibility affects public acceptance of EVs. This study measures the objective, perceived and prospective accessibility of public EV charging facilities, investigating how and to what extent this novel set of accessibility measures affects the EV adoption intention of individuals. The data are primarily derived from a recent questionnaire survey of driver license holders in Hong Kong administered to both EV owners and non-EV owners. Objective accessibility is measured by the number of (population-weighted) Tesla and standard chargers publicly available within five minutes walking distance of an individual’s residential district and subjective (i.e., perceived and prospective) accessibility is measured by four Likert-scale questions. The results show that objective accessibility significantly and substantially influences an individual’s intention to purchase an EV. Meanwhile, both perceived and prospective accessibility are highly significant for the adoption intention of non-EV owners. We also observe significant effects for perceived and prospective driving ranges, environmental consciousness and prior experience with EVs. This study provides a valuable reference for the impact of the accessibility of public EV chargers on EV adoption in the context of a high-density Asian city. Based on the findings, we propose various policy recommendations that integrate accessibility planning strategies into EV promotion in cities that aspire to expand e-mobility.